The 2014 ACM International Conference on Measurement and Modeling of Computer Systems 2014
DOI: 10.1145/2591971.2591991
|View full text |Cite
|
Sign up to set email alerts
|

On maximizing diffusion speed in social networks

Abstract: A variety of models have been proposed and analyzed to understand how a new innovation (e.g., a technology, a product, or even a behavior) diffuses over a social network, broadly classified into either of epidemic-based or game-based ones. In this paper, we consider a game-based model, where each individual makes a selfish, rational choice in terms of its payoff in adopting the new innovation, but with some noise. We study how diffusion effect can be maximized by seeding a subset of individuals (within a given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The dynamics of the spreading process have been studied in [6][7][8][9]. In [6], the information source detection under the Susceptible-Infected-Recovered (SIR) epidemic model has been considered.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The dynamics of the spreading process have been studied in [6][7][8][9]. In [6], the information source detection under the Susceptible-Infected-Recovered (SIR) epidemic model has been considered.…”
Section: Related Workmentioning
confidence: 99%
“…The authors have shown that the half-life time of virus over two simple networks of clique networks and star networks is O( log n n ) and O(log n), respectively, where n is the number of infected nodes. Besides epidemic models, a game-based model has been studied in [9], where each node can adopt the information to maximize its payoff. The work aims to find good seeds (i.e., information sources) that can maximize the diffusion speed and developed interesting seeding schemes for different network structures.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [6], the authors propose a probabilistic approach of social influence diffusion model with incentives (as uniform diffusion has been observed to be no longer valid in social networks and high degree nodes need not be the most influential in all contexts [12]); the authors propose an influence diffusion probability for each node, instead of uniform probability, and categorize nodes into two classes: active and inactive; the active nodes have chances of influencing the inactive nodes, but not vice-versa; diffusion still happens based on a system-wide threshold. Our probabilistic diffusion model is link-based (could be even run with different diffusion probability for each link) and does not use any node-based system-wide threshold to regulate the diffusion.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, the non-negative restricted Boltzmann machine (RBM), which is equivalent to FIM on complete bipartite graphs, has been studied in the context of unsupervised deep learning models [33], where non-negativity (i.e., ferromagneticity) provides non-negative matrix factorization [23] like interpretable features, which is especially useful for analyzing medical data [41,26] and document data [33]. FIM is also a popular model for studying strategic diffusion in social networks [35,29], where in this case β uv represents a friendship or other positive relationships between two individuals u, v.…”
Section: Introductionmentioning
confidence: 99%